(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
We all know that the elementary school phase is the essence of the education system. This is because almost all of the student’s abilities begin to be seen and developed at that time. Some readers begin to write poetry, others begin to prove that they have beautiful speech, others paint a picture very beautifully. Responsibility for the teacher at that time will be strong, and he should make the students look at their abilities and create conditions for them. In this article, we will discuss some of the recommendations, methods, and importance of expressive reading available in each language that helps to shape those beautiful speech entities